Gas barrier laminate and method for producing same
A transparent oxide film layer with silicon and tin on resin base materials, enhanced by a magnetron sputtering method, addresses the need for high water vapor barrier properties and transparency in gas barrier laminates, achieving superior gas barrier performance and durability.
Patent Information
- Application Number
- JP2020005362
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-17
- Filing Date
- 2020-01-16
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-01-16
AI Technical Summary
Existing gas barrier laminates using resin base materials lack the necessary high water vapor barrier properties and transparency required for applications in electronic components, despite advancements in using metal oxide films.
A transparent oxide film layer containing silicon and tin, with specific atomic ratios, is applied to a resin base material using a magnetron sputtering method with alternating electrode voltages to form a dense film, optionally accompanied by an undercoat and overcoat layer to enhance adhesion and protection.
The laminate achieves water vapor permeability of 0.01 g/(m²·day) or less and helium permeability of 4 cc/(m²·day·atm) or less, with improved transparency and resistance to mechanical stress.
Smart Images

Figure 0007618960000003 
Figure 0007618960000004 
Figure 0007618960000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas barrier laminate using a resin substrate, and a method for producing the same. [Background technology]
[0002] A gas barrier laminate is a laminate that has the property of not allowing oxygen, water vapor, etc. to pass through (gas barrier properties), and is widely used in various fields that require the blocking of various gases, such as packaging for precision electronic parts, electronics materials, food, medicine, etc.
[0003] The required gas barrier properties vary depending on the application, but generally, for sealing films for displays such as organic electroluminescence (EL) and electronic paper, a gas barrier property of 0.01 g / (m 2 In recent years, there has been an increasing demand for even higher levels of water vapor barrier properties. These films also require transparency.
[0004] In recent years, in the fields of organic electroluminescence (EL) and electronic paper, there has been a trend to use resins instead of glass as substrates for reasons such as flexibility, damage prevention, and weight reduction. However, resin substrates have poor gas barrier properties against oxygen gas and water vapor, which causes problems with the deterioration of these elements and electronic materials.
[0005] For this reason, various products have been developed to achieve high gas barrier properties and transparency using a resin substrate, and in recent years, many gas barrier laminates have been proposed in which metal oxide films such as silicon oxide and aluminum oxide, and oxynitride films of various metals are provided on a nanoscale on a resin substrate.
[0006] As a method for producing gas barrier laminates, physical film formation methods such as induction heating, resistance heating, electron beam deposition, and sputtering are being investigated because they can be easily expanded to large areas and roll-to-roll processes.
[0007] In order to achieve higher gas barrier properties, it is necessary to form a dense gas barrier layer made of an inorganic compound, and dense inorganic compound films can generally be easily produced by sputtering.
[0008] In order to achieve higher transparency, it is necessary to reduce reflection at the interface between the resin substrate and the inorganic compound film and to increase the visible light transmittance, and therefore it is necessary to form an inorganic compound film having a refractive index close to that of the resin substrate.
[0009] For example, Patent Document 1 below describes a transparent resin substrate (gas barrier laminate) that is highly transparent and has high water vapor barrier performance. In this gas barrier laminate, a transparent oxide film that contains tin oxide and silicon (Si) as an additive element in a ratio of 46 atomic % to 63 atomic % relative to the total of Si and Sn, is an amorphous film, and has a refractive index of 1.75 or less at a wavelength of 633 nm, is formed as a gas barrier layer on at least one surface of a resin substrate by a direct current (DC) pulse sputtering method.
[0010] However, the gas barrier laminate has a water vapor transmission rate of 0.01 g / (m2) measured by the Mocon method in accordance with JIS K7129. 2 ·days), which is certainly a high level of water vapor gas barrier property; however, in order to meet the higher standards of water vapor barrier property that have been required in recent years, further improvements are required. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Patent No. 4788463 Summary of the Invention [Problem to be solved by the invention]
[0012] Therefore, an object of the present invention is to provide a transparent gas barrier laminate having good water vapor barrier properties and using a resin substrate, and a method for producing the same. [Means for solving the problem]
[0013] In order to solve the above problems, the gas barrier laminate according to the present invention comprises a resin substrate and a transparent oxide film layer containing silicon (Si) and tin (Sn) on one or both sides of the resin substrate, and has a water vapor permeability of 0.01 g / (m) at a measurement condition of 40° C. and 90% RH. 2 The characteristic of this method is that it is less than 100 days.
[0014] In the gas barrier laminate according to the present invention, the helium permeability under the measurement conditions of 40° C. and 0% RH is 4 cc / (m 2 It is preferable that the temperature be less than 100°C (day atm).
[0015] In addition, in the gas barrier laminate according to the present invention, the neon transmittance under the measurement conditions of 40° C. and 0% RH is 0.5 cc / (m 2 It is preferable that the temperature be less than 100°C (day atm).
[0016] In the gas barrier laminate according to the present invention, it is preferable that the ratio of the number of silicon (Si) atoms in the transparent oxide film layer to the total number of silicon (Si) and tin (Sn) atoms (Si / (Si+Sn)) is 0.10 or more and 0.62 or less, and the ratio of the number of oxygen (O) atoms to the total number of silicon (Si) and tin (Sn) atoms (O / (Si+Sn)) is 0.80 or more and 2.00 or less.
[0017] In the gas barrier laminate according to the present invention, the transparent oxide film layer may contain at least one element selected from the group consisting of Al, Ga, Ge, Nb, Ta, W, Zn and Ti.
[0018] In the gas barrier laminate according to the present invention, it is preferable that the ratio (O / (Si+Sn+α)) of the total atomic number of oxygen (O) in the transparent oxide film layer to the total atomic number of silicon (Si), tin (Sn) and at least one element α selected from Al, Ga, Ge, Nb, Ta, W, Zn and Ti is 0.90 or more and 2.50 or less, the ratio (Si / (Sn+α)) of the total atomic number of silicon (Si) to tin (Sn) and the element α is 0.10 or more and 3.50 or less, and the content (atm %) of the element α is equal to or less than the content (atm %) of silicon (Si).
[0019] In the gas barrier laminate according to the present invention, the transparent oxide film layer may contain nitrogen (N).
[0020] In the gas barrier laminate according to the present invention, it is preferable that the refractive index n of the deposited transparent oxide film layer is 1.45 or more and 1.95 or less, and the optical thickness nd expressed as the product of the film thickness d and the refractive index n is 14.5 or more and 975 or less.
[0021] Furthermore, the gas barrier laminate according to the present invention has an undercoat layer between the resin substrate and the transparent oxide film layer, and the undercoat layer may be formed from at least one of a thermosetting resin, a thermoplastic resin, an ultraviolet-curable resin, and an electron beam-curable resin.
[0022] Furthermore, the gas barrier laminate according to the present invention has an overcoat layer on the outer side of the transparent oxide film layer, and the overcoat layer may be formed from at least one of a thermosetting resin, a thermoplastic resin, an ultraviolet-curable resin, and an electron beam-curable resin.
[0023] The method for producing the gas barrier laminate according to the present invention is characterized in that a transparent oxide film layer is formed by using a magnetron sputtering apparatus in which two electrodes are positioned in parallel, and alternately positive and negative voltages can be applied to each electrode, with each electrode alternately serving as a cathode and an anode.
[0024] In the method for producing the gas barrier laminate according to the present invention, the transparent oxide film layer may be formed by using a magnetron sputtering device equipped with a cylindrical, rotatable cathode electrode.
[0025] In addition, in the method for producing the gas barrier laminate according to the present invention, the transparent oxide film layer may be formed by using a magnetron sputtering apparatus in which two cylindrical rotatable cathode electrodes are positioned in parallel, and alternately positive and negative voltages can be applied to each electrode, with each electrode alternately serving as a cathode and an anode.
[0026] In the method for producing the gas barrier laminate according to the present invention, the film-forming pressure when forming the transparent oxide layer is preferably 0.05 Pa or more and 0.50 Pa or less. Effect of the Invention
[0027] According to the present invention, it is possible to provide a transparent gas barrier laminate having good water vapor barrier properties and using a resin substrate, and a method for producing the same. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 is a cross-sectional view of a gas barrier laminate according to a first embodiment of the present invention. [Diagram 2] FIG. 3 is a cross-sectional view of a gas barrier laminate according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of a gas barrier laminate according to a third embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] First Embodiment A first embodiment of the present invention will be described below with reference to the accompanying drawings. 1, the gas barrier laminate according to this embodiment is composed of a resin substrate 11 and a transparent oxide film layer 13 formed on one side of the resin substrate 11. In practice, the transparent oxide film layer 13 may be laminated on both sides of the resin substrate 11. In the following description, the transparent oxide film layer formed (laminated) on the resin substrate 11 and the transparent oxide film layer 13 are synonymous.
[0030] (Resin substrate) The resin substrate 11 is not particularly limited, and known materials can be used. For example, polyolefins (polyethylene, polypropylene, etc.), polyesters (polyethylene terephthalate, polyethylene naphthalate, etc.), polyimides, polyamides (nylon-6, nylon-66, etc.), polystyrene, ethylene vinyl alcohol, polyvinyl chloride, polyimide, polyvinyl alcohol, polycarbonate, polyethersulfone, acrylic, celluloses (triacetyl cellulose, diacetyl cellulose, etc.), etc. can be mentioned, but are not particularly limited to these. In practice, it is desirable to select appropriately depending on the application and required physical properties, and for packaging to protect contents that are extremely sensitive to moisture, such as electronic components and optical components, it is desirable to use substrates that themselves have high gas barrier properties, such as polyethylene naphthalate, polyimides, and polyethersulfone, but are not limited to these examples.
[0031] Although there are no limitations on the thickness of the resin base material 11, a thickness of about 12 μm to 300 μm is easily used depending on the application. Resin base material 11 having a thickness within this range is preferable because it is flexible and can be wound into a roll.
[0032] The resin substrate 11 may be in the form of a continuous material or a sheet material, but a continuous substrate is preferably used. The length of the continuous resin substrate 11 in the longitudinal direction is not particularly limited, but a continuous film of, for example, 10 m or more is preferably used. The upper limit of the length is not limited, and it may be, for example, about 10 km.
[0033] The surface of the resin substrate 11 may contain additives such as antistatic agents, ultraviolet absorbers, plasticizers, and slipping agents, if necessary. Furthermore, in order to enhance adhesion, the surface of the substrate may be subjected to physical treatments such as corona treatment, frame treatment, plasma treatment, and adhesion enhancing treatment, or chemical treatments such as chemical treatments with acids or alkalis. The substrate surface contributes to the denseness and adhesion in the initial growth stage of vacuum film formation, and is desirably smooth.
[0034] (Transparent oxide film layer) The transparent oxide film layer 13 is a transparent oxide film containing silicon (Si) and tin (Sn) that is provided to impart gas barrier properties to the entire gas barrier laminate, and is formed by a sputtering method using a magnetron sputtering device in which two electrodes are positioned in parallel, and alternate positive and negative voltages can be applied to each electrode, with each electrode alternately serving as a cathode and an anode.
[0035] The transparent oxide film layer 13 is configured so that the ratio of the number of silicon (Si) atoms to the total number of silicon (Si) atoms and tin (Sn) atoms (Si / (Si+Sn)) is 0.10 or more and 0.62 or less, and the ratio of the number of oxygen (O) atoms to the total number of silicon (Si) atoms and tin (Sn) atoms (O / (Si+Sn)) is 0.80 or more and 2.00 or less. In consideration of the refractive index and gas barrier properties, the ratio of the number of silicon (Si) atoms to the total number of silicon (Si) atoms and tin (Sn) atoms (Si / (Si+Sn)) is more preferably 0.50 or more and 0.62 or less. As a method for determining whether the transparent oxide film layer 13 is within the above composition range, a conventionally known method can be used, and for example, it can be evaluated based on the results obtained by an analysis device such as an XPS (X-ray photoelectron spectrometer).
[0036] By setting the film composition of the transparent oxide film layer 13 within the above range, the refractive index n becomes 1.45 or more and 1.95 or less, and a refractive index n close to that of the resin substrate 11 can be obtained. Therefore, reflection at the interface between the resin substrate 11 and the transparent oxide film layer 13 is small, and the light transmittance of visible light can be increased. The refractive index of the transparent oxide film layer 13 can be measured and evaluated by measuring the refractive index of a film having the same composition as the transparent oxide film layer 13 with a refractometer (ellipsometer).
[0037] The thickness of the transparent oxide film layer 13 is preferably 5 nm or more and 500 nm or less. If it is less than 5 nm, the transparent oxide film layer 13 cannot cover the entire substrate film, and sufficient gas barrier properties cannot be obtained. If it exceeds 500 nm, cracks are likely to occur, and the gas barrier properties may be reduced. Furthermore, costs increase due to an increase in the amount of material used and a longer film formation time, which is not preferable from an economical point of view. In other words, it is preferable that the optical thickness nd, which is expressed by the product of the thickness d (nm) and the refractive index n, is 14.5 to 975.
[0038] The transparent oxide film layer 13 may contain at least one element selected from Al, Ga, Ge, Nb, Ta, W, Zn, and Ti in addition to the metal elements silicon (Si) and tin (Sn). When the transparent oxide film layer 13 contains at least one element selected from Al, Ga, Ge, Nb, Ta, W, Zn, and Ti in addition to silicon (Si) and tin (Sn), it is possible to improve the gas barrier properties, improve the adhesion to the resin substrate 11, improve the temperature and humidity durability, and adjust the refractive index n. The transparent oxide film layer 13 may contain nitrogen in addition to the above-mentioned metal element group, and may be a transparent oxynitride film layer.
[0039] Furthermore, when the transparent oxide film layer 13 contains at least one element α selected from Al, Ga, Ge, Nb, Ta, W, Zn, and Ti in addition to silicon (Si) and the metal elements of silicon (Si) and tin (Sn), taking into consideration the refractive index and gas barrier properties, it is preferable that the ratio of the total atomic number of oxygen (O) in the transparent oxide film layer to the total atomic number of silicon (Si), tin (Sn), and the element α (O / (Si+Sn+α)) is 0.90 or more and 2.50 or less, the ratio of the total atomic number of silicon (Si), tin (Sn), and the element α (Si / (Si+Sn)) is 0.10 or more and 3.50 or less, and the content (atm %) of the element α is equal to or less than the content (atm %) of silicon (Si).
[0040] (Sputtering method) The means for forming the transparent oxide film layer 13 is a sputtering method using a magnetron sputtering device in which two electrodes are placed in parallel, and a positive and negative voltage can be applied alternately to each electrode, with each electrode alternately playing the role of a cathode and an anode. This sputtering method is a method in which a target of a material is placed on two electrodes placed in a vacuum chamber, and a high voltage is applied to cause an ionized rare gas element (usually argon) to collide with the target, ejecting atoms from the target surface, and the target element is attached to the resin substrate 11, thereby forming the transparent oxide film layer 13. At this time, a predetermined amount of oxygen gas is flowed into the chamber, and the element ejected from the target reacts with oxygen to form the transparent oxide film layer 13. Furthermore, at this time, a transparent oxynitride film layer may be formed by flowing nitrogen gas simultaneously with the oxygen gas. In addition, a target made of an alloy of Si and Sn is used as the target. The target may contain, in addition to Si and Sn, at least one element selected from Al, Ga, Ge, Nb, Ta, W, Zn, and Ti (hereinafter referred to as element α).
[0041] In this sputtering method, the anode and cathode are alternately switched between two targets, so that while one target is discharging and forming a film, the other target is charged with a weak opposite charge, and the charging of the target surface is eliminated. Therefore, damage to the film caused by arcing can be suppressed more than in the DC sputtering method or the DC pulse sputtering method, and it is possible to form a high-quality film more stably. At this time, the power source for applying a voltage to the electrode is not particularly specified, and may be either alternating current (AC) or DC, but it is preferable to use a DC pulse power source. This is because a pulse wave of the applied voltage is more effective in mitigating charge-up at the anode during the off time of the voltage application. The frequency of the DC pulse power source is not particularly limited and can be set appropriately. It is preferably 1 kHz or more and 100 kHz or less, and more preferably 10 kHz or more and 50 kHz or less.
[0042] Alternatively, the means for forming the transparent oxide film layer 13 may be a sputtering method using a magnetron sputtering device equipped with a cylindrical, rotatable cathode electrode. In this sputtering method, the target shape is also cylindrical like the cathode, and the entire target surface becomes an erosion region by rotation, so that the utilization rate of the target is high and film formation can be performed continuously.
[0043] Alternatively, the transparent oxide film layer 13 may be formed by using a magnetron sputtering device in which two cylindrical rotatable cathode electrodes are positioned in parallel, and alternately positive and negative voltages can be applied to each electrode, with each electrode alternately functioning as a cathode and an anode.
[0044] In the method for producing a gas barrier laminate according to the present invention, the deposition pressure when depositing the transparent oxide layer is preferably 0.05 Pa or more and 0.50 Pa or less. By depositing the film at a sputtering deposition pressure of 0.05 Pa or more and 0.50 Pa or less, a film with few surface defects can be obtained.
[0045] The gas barrier laminate according to this embodiment is constructed by laminating the above-mentioned transparent oxide film layer 13 on a resin substrate 11. This has a water vapor permeability of 0.01 g / (m) under measurement conditions of 40° C. and 90% RH. 2 ·day) or less. In addition, by forming the transparent oxide film layer 13 as a dense film, the helium permeability under the measurement conditions of 40° C. and 0% RH can be reduced to 4 cc / (m 2 ·day·atm) or less. In addition, the neon transmittance under the measurement conditions of 40°C and 0% RH can be reduced to 0.5cc / (m 2 ·day·atm) or less. Furthermore, by using a sputtering method using the above-mentioned magnetron sputtering device, it is possible to suppress defects in the film due to arcing and to manufacture a gas barrier laminate having a dense transparent oxide film layer 13. Therefore, according to this embodiment, a gas barrier laminate having good gas barrier properties and a manufacturing method thereof can be realized.
[0046] <Second embodiment> A second embodiment of the present invention will now be described. The gas barrier laminate according to this embodiment, like the gas barrier laminate shown in Fig. 2, is obtained by providing an undercoat layer 12 between the resin substrate 11 and the transparent oxide film layer 13 of the gas barrier laminate shown in Fig. 1. Alternatively, the gas barrier laminate may have a configuration in which the undercoat layer 12 and the transparent oxide film layer 13 are laminated in this order on both sides of the resin substrate 11.
[0047] The undercoat layer 12 is provided on the resin substrate 11 in order to increase the adhesion between the resin substrate 11 and the transparent oxide film layer 13, prevent peeling of the transparent oxide film layer 13, and protect the transparent oxide film layer 13 from mechanical damage such as scratches and abrasions. The material for forming the undercoat layer 12 is not particularly limited, but examples of the material that can be used include thermosetting resins, thermoplastic resins, ultraviolet curing resins, and electron beam curing resins.
[0048] Examples of the thermosetting resin forming the undercoat layer 12 include a thermosetting urethane resin made of an acrylic polyol and an isocyanate prepolymer, a phenol resin, a urea melamine resin, an epoxy resin, an unsaturated polyester resin, a silicone resin, etc. Among them, by forming the undercoat layer 12 using a composite of an acrylic polyol containing an OH group and an isocyanate compound having at least two or more NCO groups in the molecule, the adhesion between the resin substrate 11 and the transparent oxide film layer 13 can be improved.
[0049] An acrylic polyol is a polymer compound obtained by polymerizing a (meth)acrylic acid derivative monomer, or a polymer compound obtained by copolymerizing a (meth)acrylic acid derivative monomer with other monomers, which has OH groups at the end and side chains and reacts with the NCO group of an isocyanate compound. The (meth)acrylic acid derivative monomer has OH groups at the end and side chains. Examples of the (meth)acrylic acid derivative monomer include hydroxyethyl (meth)acrylate and hydroxybutyl (meth)acrylate.
[0050] The above other monomers can be copolymerized with the (meth)acrylic acid derivative monomer having an OH group at the end and at the side chain. Examples of the above other monomers include (meth)acrylic acid derivative monomers having an alkyl group at the side chain, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and t-butyl (meth)acrylate, (meth)acrylic acid derivative monomers having a COOH group at the side chain, such as (meth)acrylic acid, and (meth)acrylic acid derivative monomers having an aromatic ring or a cyclic structure at the side chain, such as benzyl (meth)acrylate and cyclohexyl (meth)acrylate. Other than the (meth)acrylic acid derivative monomers, styrene monomers, cyclohexyl maleimide monomers, and phenyl maleimide monomers are possible. The above other monomers may themselves have an OH group at the end and at the side chain.
[0051] The acrylic polyol is preferably a polymer compound obtained by polymerizing a (meth)acrylic acid derivative monomer having a COOH group in the side chain, such as (meth)acrylic acid. When forming the undercoat layer 12, a composite of an acrylic polyol obtained by polymerizing a monomer having a COOH group and an isocyanate compound can be used to obtain a gas barrier laminate film having higher water vapor barrier properties.
[0052] The OH-containing acrylic polyol that can be used for the undercoat layer 12 is not particularly limited, but the OH value is preferably 50 mgKOH / g or more and 250 mgKOH / g or less. Here, the OH value (mgKOH / g) is an index of the amount of OH groups in the acrylic polyol, and indicates the number of mg of potassium hydroxide required to acetylate the OH groups in 1 g of the acrylic polyol. The weight-average molecular weight of the acrylic polyol is not particularly limited, but is preferably 3000 or more and 200,000 or less. In particular, it is preferably 5000 or more and 100,000 or less. Furthermore, it is more preferably 5000 or more and 40,000 or less.
[0053] An isocyanate compound has two or more NCO groups in its molecule. Examples of monomeric isocyanates include aromatic isocyanates such as tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), xylene diisocyanate (XDI), and tetramethylxylylene diisocyanate (TMXDI), and aliphatic isocyanates such as hexamethylene diisocyanate (HDI), bisisocyanate methylcyclohexane (H6XDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (H12MDI). Polymers or derivatives of these monomeric isocyanates can also be used. For example, there are trimer nurate types, adduct types reacted with 1,1,1-trimethylolpropane, and biuret types reacted with biuret.
[0054] The isocyanate compound may be arbitrarily selected from the above-mentioned isocyanate compounds or their polymers and derivatives, and one or a combination of two or more kinds may be used.
[0055] An example of the undercoat layer 12 is formed by applying a solution consisting of a composite of the above-mentioned acrylic polyol and the above-mentioned isocyanate compound and a solvent onto the resin substrate 11, and then reacting and curing the solution. The equivalent ratio (NCO / OH) of the NCO group of the isocyanate compound to the OH group of the acrylic polyol is preferably 0.3 or more and 2.5 or less. The solvent used here may be any solvent that dissolves the above-mentioned acrylic polyol and the isocyanate compound. Examples of the solvent include methyl acetate, ethyl acetate, butyl acetate, cyclohexanone, acetone, methyl ethyl ketone, dioxolane, tetrahydrofuran, etc. In practice, one or more of these solvents may be used in combination.
[0056] The thermoplastic resin forming the undercoat layer 12 is appropriately selected from polyols having two or more OH groups, such as acrylic polyol, polyester polyol, polycarbonate polyol, polyether polyol, polycaprolactone polyol, and epoxy polyol, polyvinyl resins such as polyvinyl acetate and polyvinyl chloride, polyvinylidene chloride resin, polystyrene resin, polyethylene resin, polypropylene resin, and polyurethane resin. Furthermore, these may be mixed at any ratio. The OH value of the polyol is not particularly limited, but is preferably 10 mgKOH / g or more and 250 mgKOH / g or less.
[0057] The ultraviolet-curable resin or electron-beam-curable resin forming the undercoat layer 12 is not particularly limited, but preferably contains at least a resin having an OH value in the range of 10 to 100 mgKOH / g as an organic polymer resin. Also, it is not particularly limited, but it is preferable that the organic polymer resin contains at least a resin having an acid value in the range of 10 to 100 mgKOH / g. Here, the acid value (mgKOH / g) indicates the number of mg of potassium hydroxide required to neutralize free fatty acid, resin acid, etc. contained in 1 g of sample. Also, it is preferable that the organic polymer resin contains at least a thermoplastic resin. If the OH value or acid value is less than 10 mgKOH / g, the chemical bonding strength between the functional group and the surface of the transparent oxide film layer 13 becomes weak, and the adhesion to the transparent oxide film layer 13 tends to be low. If the OH group value or acid value exceeds 100 mgKOH / g, precipitates containing OH groups produced by decomposition of the undercoat layer 12 during durability tests such as moist heat resistance tests tend to hinder adhesion between the undercoat layer 12 and the transparent oxide film layer 13.
[0058] Monomers that can be used in the ultraviolet curable resin or electron beam curable resin that forms the undercoat layer 12 include, for example, monofunctional monomers such as ethyl (meth)acrylate, ethylhexyl (meth)acrylate, styrene, methylstyrene, and N-vinylpyrrolidone, as well as polyfunctional monomers such as trimethylolpropane (meth)acrylate, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol (meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and neopentyl glycol (meth)acrylate. Oligomers that can be used in the ultraviolet curable resin or electron beam curable resin include urethane acrylate, epoxy acrylate, and polyester acrylate.
[0059] When two or more types of organic polymer resins selected from thermosetting resins, thermoplastic resins, ultraviolet curable resins, and electron beam curable resins are used in combination as the organic polymer resins forming the undercoat layer 12, the compounding ratio thereof is not particularly limited.
[0060] The undercoat layer 12 may further contain additives other than the organic polymer resin as necessary, such as antioxidants, weathering agents, heat stabilizers, lubricants, crystal nucleating agents, ultraviolet absorbers, plasticizers, antistatic agents, colorants, fillers, surfactants, and silane coupling agents.
[0061] The thickness of the undercoat layer 12 is preferably 0.05 μm or more and 7.0 μm or less. In particular, it is preferably 0.05 μm or more and 0.3 μm or less. If it is thinner than 0.05 μm, the adhesion between the resin substrate 11 and the transparent oxide film layer 13 becomes insufficient. If it is thicker than 7.0 μm, the influence of internal stress becomes large, the transparent oxide film layer 13 is not laminated neatly, the barrier property is not sufficiently expressed, and further, the transparency and coating accuracy are also insufficient.
[0062] The undercoat layer 12 can be formed by a normal coating method. For example, well-known methods such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset, and organic deposition can be used. As the drying method, one or more methods of applying heat such as hot air drying, heat roll drying, high frequency irradiation, infrared irradiation, UV irradiation, and electron beam irradiation can be used in combination. In addition, a film previously coated on another resin substrate by the above-mentioned forming method may be transferred to the resin substrate 11 by a transfer method such as adhesive transfer, heat transfer, and UV transfer.
[0063] <Third embodiment> A third embodiment of the present invention will now be described. The gas barrier laminate of this embodiment, like the gas barrier laminate shown in FIG. 3, has an overcoat layer 14 provided on the transparent oxide film layer 13 of the gas barrier laminate of FIG. 1 or FIG. 2.
[0064] The overcoat layer 14 is a layer containing an organic polymer resin, and is provided to protect the transparent oxide film layer 13 and prevent the occurrence of cracks due to rubbing or bending.
[0065] The organic polymer resin contained in the overcoat layer 14 can be appropriately selected, and for example, one or more types selected from a thermosetting resin, a thermoplastic resin, an ultraviolet curable resin, and an electron beam curable resin can be used. The proportion of the organic polymer resin in the overcoat layer 14 is not particularly limited and can be appropriately set.
[0066] Examples of the thermosetting resin forming the overcoat layer 14 include a thermosetting urethane resin made of an acrylic polyol and an isocyanate prepolymer, a phenol resin, a urea melamine resin, an epoxy resin, an unsaturated polyester resin, a silicone resin, etc. Among them, by forming the overcoat layer 14 using a composite of an acrylic polyol containing an OH group and an isocyanate compound having at least two or more NCO groups in the molecule, the adhesion between the overcoat layer 14 and the transparent oxide film layer 13 can be improved.
[0067] An acrylic polyol is a polymer compound obtained by polymerizing a (meth)acrylic acid derivative monomer, or a polymer compound obtained by copolymerizing a (meth)acrylic acid derivative monomer with other monomers, which has OH groups at the end and side chains and reacts with the NCO group of an isocyanate compound. The (meth)acrylic acid derivative monomer has OH groups at the end and side chains. Examples of the (meth)acrylic acid derivative monomer include hydroxyethyl (meth)acrylate and hydroxybutyl (meth)acrylate.
[0068] The above other monomers can be copolymerized with the (meth)acrylic acid derivative monomer having an OH group at the end and at the side chain. Examples of the above other monomers include (meth)acrylic acid derivative monomers having an alkyl group at the side chain, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and t-butyl (meth)acrylate, (meth)acrylic acid derivative monomers having a COOH group at the side chain, such as (meth)acrylic acid, and (meth)acrylic acid derivative monomers having an aromatic ring or a cyclic structure at the side chain, such as benzyl (meth)acrylate and cyclohexyl (meth)acrylate. Other than the (meth)acrylic acid derivative monomers, styrene monomers, cyclohexyl maleimide monomers, and phenyl maleimide monomers are possible. The above other monomers may themselves have an OH group at the end and at the side chain.
[0069] The acrylic polyol is preferably a polymer compound obtained by polymerizing a (meth)acrylic acid derivative monomer having a COOH group in the side chain, such as (meth)acrylic acid. When forming the undercoat layer 12, a composite of an acrylic polyol obtained by polymerizing a monomer having a COOH group and an isocyanate compound can be used to obtain a gas barrier laminate film having higher water vapor barrier properties.
[0070] The OH-containing acrylic polyol of the overcoat layer 14 is not particularly limited, but the OH value is preferably 50 mgKOH / g or more and 250 mgKOH / g or less. The weight average molecular weight of the acrylic polyol is not particularly limited, but specifically, it is preferably 3000 or more and 200000 or less. In particular, it is preferably 5000 or more and 100000 or less. Furthermore, it is more preferably 5000 or more and 40000 or less.
[0071] An isocyanate compound has two or more NCO groups in its molecule. Examples of monomeric isocyanates include aromatic isocyanates such as tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), xylene diisocyanate (XDI), and tetramethylxylylene diisocyanate (TMXDI), and aliphatic isocyanates such as hexamethylene diisocyanate (HDI), bisisocyanate methylcyclohexane (H6XDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (H12MDI). Polymers or derivatives of these monomeric isocyanates can also be used. For example, there are trimer nurate types, adduct types reacted with 1,1,1-trimethylolpropane, and biuret types reacted with biuret.
[0072] The isocyanate compound may be arbitrarily selected from the above-mentioned isocyanate compounds or their polymers and derivatives, and one or a combination of two or more kinds may be used.
[0073] The overcoat layer 14 is formed, for example, by applying a solution consisting of a compound of the above-mentioned acrylic polyol and the above-mentioned isocyanate compound and a solvent onto the resin substrate 11, and then reacting and curing the solution. The equivalent ratio (NCO / OH) of the NCO group of the isocyanate compound to the OH group of the acrylic polyol is preferably 0.3 or more and 2.5 or less. The solvent used here may be any solvent that dissolves the above-mentioned acrylic polyol and the isocyanate compound. Examples of the solvent include methyl acetate, ethyl acetate, butyl acetate, cyclohexanone, acetone, methyl ethyl ketone, dioxolane, tetrahydrofuran, etc. In practice, one or more of these solvents may be used in combination.
[0074] The thermosetting resin forming the overcoat layer 14 may contain, in addition to the above, at least one selected from the group consisting of a water-soluble polymer having an OH group, an alkoxysilane, and a hydrolyzate thereof.
[0075] The water-soluble polymer having OH groups is preferably polyvinyl alcohol, polycarboxylic acid, starch, or cellulose. In particular, when polyvinyl alcohol (hereinafter referred to as PVA) is used in the coating agent of the present invention, the gas barrier property is excellent. Since PVA is a polymer containing the most OH groups in the monomer unit, it has a very strong hydrogen bond with the OH group of the organosilicon compound after hydrolysis. The PVA referred to here is generally obtained by saponifying polyvinyl acetate, and includes so-called partially saponified PVA in which several tens of percent of acetate groups remain, and fully saponified PVA in which only a few percent of acetate groups remain. The molecular weight of PVA has a wide variety of polymerization degrees ranging from 300 to several thousand, but there is no problem with the effect regardless of the molecular weight. However, in general, PVA with a high saponification degree and a high molecular weight with a high polymerization degree is preferred because it has high water resistance.
[0076] In addition, alkoxysilane may be tetraethoxysilane, tetramethoxysilane, tetrapropoxysilane, methyltriethoxysilane, methyltrimethoxysilane, or the like. In addition, the hydrolysis product of alkoxysilane may be prepared by dissolving alkoxysilane in alcohol such as methanol, adding an aqueous solution of acid such as hydrochloric acid to the solution, and carrying out a hydrolysis reaction. By the hydrolysis reaction, the alkoxy group bonded to the silicon atom becomes an OH group, and the OH group is dehydrated and condensed to form a siloxane bond, thereby forming a dense and strong network polymerized coating. Therefore, an overcoat layer 14 having excellent heat resistance, water resistance, moisture resistance, bending resistance, stretch resistance, and the like can be obtained.
[0077] A silane coupling agent may be added to improve adhesion to the transparent oxide film layer 13. Examples of the silane coupling agent include those having an epoxy group such as 3-glycidoxypropyltrimethoxysilane, those having an amino group such as 3-aminopropyltrimethoxysilane, those having a mercapto group such as 3-mercaptopropyltrimethoxysilane, and those having an NCO group such as 3-isocyanatepropyltriethoxysilane, and these silane coupling agents can be used alone or in combination of two or more.
[0078] The thermoplastic resin forming the overcoat layer 14 is appropriately selected from polyols having two or more OH groups, such as acrylic polyol, polyester polyol, polycarbonate polyol, polyether polyol, polycaprolactone polyol, and epoxy polyol, polyvinyl resins such as polyvinyl acetate and polyvinyl chloride, polyvinylidene chloride resin, polystyrene resin, polyethylene resin, polypropylene resin, and polyurethane resin. Furthermore, these may be mixed in any ratio. The OH value of the polyol is not particularly limited, but is preferably 10 mgKOH / g or more and 250 mgKOH / g or less.
[0079] The ultraviolet curable resin or electron beam curable resin forming the overcoat layer 14 is not particularly limited, but preferably contains at least a resin having an OH group value in the range of 10 to 100 mgKOH / g as an organic polymer resin. Also, it is not particularly limited, but it is preferable that the organic polymer resin contains at least a resin having an acid value in the range of 10 to 100 mgKOH / g. Also, it is preferable that the organic polymer resin contains at least a thermoplastic resin. If the OH group value or acid value is less than 10 mgKOH / g, the chemical bonding strength between the functional group and the surface of the transparent oxide film layer 13 becomes weak, and the adhesion to the transparent oxide film layer 13 tends to be low. If the OH group value or acid value exceeds 100 mgKOH / g, precipitates containing OH groups generated by decomposition of the overcoat layer 14 in durability tests such as a moist heat resistance test tend to hinder the adhesion between the overcoat layer 14 and the transparent oxide film layer 13.
[0080] Monomers that can be used in the ultraviolet curable resin or electron beam curable resin that forms the overcoat layer 14 include, for example, monofunctional monomers such as ethyl (meth)acrylate, ethylhexyl (meth)acrylate, styrene, methylstyrene, and N-vinylpyrrolidone, as well as polyfunctional monomers such as trimethylolpropane (meth)acrylate, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol (meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and neopentyl glycol (meth)acrylate. Oligomers that can be used in the ultraviolet curable resin or electron beam curable resin include urethane acrylate, epoxy acrylate, and polyester acrylate.
[0081] When two or more types of organic polymer resins selected from a thermosetting resin, a thermoplastic resin, an ultraviolet-curable resin, and an electron beam-curable resin are used in combination as the organic polymer resin forming the overcoat layer 14, the compounding ratio thereof is not particularly limited.
[0082] The overcoat layer 14 may further contain additives other than the organic polymer resin as necessary, such as antioxidants, weathering agents, heat stabilizers, lubricants, crystal nucleating agents, ultraviolet absorbers, plasticizers, antistatic agents, colorants, fillers, surfactants, and silane coupling agents.
[0083] The thickness of the overcoat layer 14 is not particularly limited and can be set appropriately. It is preferably 0.001 μm or more and 7.0 μm or less. If it is thinner than 0.001 μm, the protection of the transparent oxide film layer 13 is insufficient, and if it is thicker than 7.0 μm, the effect of internal stress becomes large, causing cracks.
[0084] The overcoat layer 14 can be formed by a normal coating method, as in the case of the undercoat layer 12. For example, well-known methods such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset, and organic deposition can be used. As the drying method, one or more heat application methods such as hot air drying, heat roll drying, high frequency irradiation, infrared irradiation, UV irradiation, and electron beam irradiation can be used in combination. In addition, a film previously coated on another resin substrate by the above-mentioned formation method may be transferred to the transparent oxide film layer 13 by a transfer method such as adhesive transfer, heat transfer, and UV transfer. EXAMPLES
[0085] EXAMPLES The gas barrier laminate according to the present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0086] In Example 1, Comparative Example 1, and Comparative Example 3, a transparent oxide film layer 13 is provided on one side of the resin substrate 11. In Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, Example 12, Example 13, Example 14, Example 15, Example 16, Example 17, Example 18, Example 19, Example 20, Example 21, Example 22, Example 23, Example 24, Example 25, Example 26, Example 27, Example 28, Example 29, Example 30, Example 31, Example 32, Example 33, Example 34, Example 35, and Comparative Example 2, an undercoat layer 12 is further provided between the resin substrate 11 and the transparent oxide film layer 13. In Example 3, an overcoat layer 14 is further provided on the transparent oxide film layer 13. That is, Example 1, Comparative Example 1, and Comparative Example 3 correspond to the gas barrier laminate shown in FIG. 1. Example 2, Example 4, Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, Example 12, Example 13, Example 14, Example 15, Example 16, Example 17, Example 18, Example 19, Example 20, Example 21, Example 22, Example 23, Example 24, Example 25, Example 26, Example 27, Example 28, Example 29, Example 30, Example 31, Example 32, Example 33, Example 34, Example 35 and Comparative Example 2 correspond to the gas barrier laminate shown in Figure 2. Example 3 corresponds to the gas barrier laminate shown in Figure 3.
[0087] <Example 1> [Resin substrate placement process] As the resin substrate 11, a biaxially stretched PET film having a thickness of 50 μm (manufactured by Toray Industries, Inc., product name "Lumirror T60") was used.
[0088] [Transparent oxide film layer stacking process] A transparent oxide film layer 13 was formed on one side of a resin substrate 11 by a sputtering method (referred to as method A) using a magnetron sputtering device in which two electrodes were placed in parallel, and a voltage could be applied alternately between positive and negative, with each electrode acting alternately as a cathode and an anode. The film formation conditions were a film formation pressure of 0.3 Pa and a power density of 3.3 W / cm. 2The target was an alloy target of Si and Sn (atomic composition ratio Si:Sn=50:50). An MF power supply was used as a means for applying power to the two electrodes. A rectangular voltage with a frequency of 40 kHz was applied to the two electrodes positioned in parallel. Argon gas and oxygen gas were used as gases. The flow rate of oxygen gas was controlled by detecting the emission intensity of the plasma and the voltage value of the discharge so that the state of the target surface was in a transition state in the middle of transitioning from the metal mode to the oxide mode. A gas barrier laminate was obtained by forming a transparent oxide film layer 13 with a thickness of 100 nm.
[0089] <Example 2> [Resin substrate placement process] As in Example 1, a biaxially stretched PET film having a thickness of 50 μm (manufactured by Toray Industries, Inc., product name "Lumirror T60") was used as the resin substrate 11.
[0090] [Preparation and coating process of the solution for the undercoat layer] As a solution for the undercoat layer 12, an acrylic polyol (weight average molecular weight 10×10) obtained by copolymerizing hydroxyethyl methacrylate (HEMA) and methyl methacrylate (MMA) as monomers was used. 3 A 5% methyl ethyl ketone solution was prepared by mixing 1 equivalent of an HDI nurate type isocyanate curing agent relative to the amount of OH groups in the main agent with the main agent. The solution prepared above was then applied onto a resin substrate 11, and an undercoat layer 12 having a thickness of 300 nm after drying was laminated thereon.
[0091] [Transparent oxide film layer stacking process] Under the same sputtering conditions as in Example 1, a transparent oxide film layer 13 having a thickness of 100 nm was formed on the undercoat layer 12, thereby obtaining a gas barrier laminate.
[0092] <Example 3> [Resin substrate placement process] As in Examples 1 and 2, a biaxially stretched PET film having a thickness of 50 μm (manufactured by Toray Industries, Inc., product name "Lumirror T60") was used as the resin substrate 11.
[0093] [Preparation and coating process of the solution for the undercoat layer] As in Example 2, an undercoat layer 12 having a thickness of 300 nm after drying was laminated on a resin substrate 11.
[0094] [Transparent oxide film layer stacking process] The sputtering conditions were the same as those in Examples 1 and 2, and a transparent oxide film layer 13 having a thickness of 100 nm was formed on the undercoat layer 12 .
[0095] [Preparation and coating process of the solution for the overcoat layer] A solution with a solid content of 5 mass % was prepared as a solution for the overcoat layer 14 by mixing a hydrolyzed solution of tetraethoxysilane (TEOS) and an aqueous solution of polyvinyl alcohol (PVA) so that the solid content ratio after drying would be 70:30. Thereafter, the above-prepared solution was applied onto the transparent oxide film layer 13 by spin coating, and an overcoat layer 14 with a thickness of 300 nm after drying was laminated, thereby obtaining a gas barrier laminate.
[0096] <Example 4> A gas barrier laminate was obtained in the same manner as in Example 2, except that an alloy target of Si and Sn (atomic composition ratio Si:Sn=10:90) was used.
[0097] <Example 5> A gas barrier laminate was obtained in the same manner as in Example 2, except that an alloy target of Si and Sn (atomic composition ratio Si:Sn=30:70) was used.
[0098] <Example 6> A gas barrier laminate was obtained in the same manner as in Example 2, except that an alloy target of Si and Sn (atomic composition ratio Si:Sn=62:38) was used.
[0099] <Example 7> A gas barrier laminate was obtained in the same manner as in Example 2, except that an alloy target of Si and Sn (atomic composition ratio Si:Sn=70:30) was used.
[0100] <Example 8> The sputtering conditions were as follows: the deposition pressure was set to 0.50 Pa. A gas barrier laminate was obtained in the same manner as in Example 2.
[0101] <Example 9> The sputtering conditions were as follows: the deposition pressure was set to 0.05 Pa. A gas barrier laminate was obtained in the same manner as in Example 2.
[0102] <Example 10> A gas barrier laminate was obtained in the same manner as in Example 2, except that the transparent oxide film layer 13 was formed by a sputtering method (referred to as method C) using a magnetron sputtering device equipped with a cylindrical rotatable cathode electrode. A DC power supply was used as a means for supplying power to the electrode.
[0103] <Example 11> A gas barrier laminate was obtained in the same manner as in Example 2, except that the transparent oxide film layer 13 was formed by a sputtering method (referred to as Method D) using a magnetron sputtering device in which two cylindrical rotatable electrodes were positioned in parallel, alternating positive and negative voltages could be applied to each electrode, and each electrode alternately served as a cathode and an anode.
[0104] <Example 12> A gas barrier laminate was obtained under the same conditions as in Example 2, except that argon gas, oxygen gas, and nitrogen gas were used as the introduced gases in the sputtering conditions.
[0105] <Example 13> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Al (atomic composition ratio Si:Sn:Al=76:12:12) was used.
[0106] <Example 14> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Al (atomic composition ratio Si:Sn:Al=50:38:12) was used.
[0107] <Example 15> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Al (atomic composition ratio Si:Sn:Al=31:38:31) was used.
[0108] <Example 16> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ga (atomic composition ratio Si:Sn:Ga=76:12:12) was used.
[0109] <Example 17> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ga (atomic composition ratio Si:Sn:Ga=50:38:12) was used.
[0110] <Example 18> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ga (atomic composition ratio Si:Sn:Ga=31:38:31) was used.
[0111] <Example 19> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ge (atomic composition ratio Si:Sn:Ge=76:12:12) was used.
[0112] <Example 20> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ge (atomic composition ratio Si:Sn:Ge=50:38:12) was used.
[0113] <Example 21> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ge (atomic composition ratio Si:Sn:Ga=31:38:31) was used.
[0114] <Example 22> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Nb (atomic composition ratio Si:Sn:Nb=76:12:12) was used.
[0115] <Example 23> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Nb (atomic composition ratio Si:Sn:Nb=50:38:12) was used.
[0116] <Example 24> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Nb (atomic composition ratio Si:Sn:Nb=31:38:31) was used.
[0117] <Example 25> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ta (atomic composition ratio Si:Sn:Ta=76:12:12) was used.
[0118] <Example 26> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ta (atomic composition ratio Si:Sn:Ta=50:38:12) was used.
[0119] <Example 27> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ta (atomic composition ratio Si:Sn:Ta=31:38:31) was used.
[0120] <Example 28> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and W (atomic composition ratio Si:Sn:W=76:12:12) was used.
[0121] <Example 29> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and W (atomic composition ratio Si:Sn:W=50:38:12) was used.
[0122] <Example 30> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and W (atomic composition ratio Si:Sn:W=31:38:31) was used.
[0123] <Example 31> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Zn (atomic composition ratio Si:Sn:Zn=76:12:12) was used.
[0124] <Example 32> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Zn (atomic composition ratio Si:Sn:Zn=50:38:12) was used.
[0125] <Example 33> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Zn (atomic composition ratio Si:Sn:Zn=31:38:31) was used.
[0126] <Example 34> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ti (atomic composition ratio Si:Sn:Ti=76:12:12) was used.
[0127] <Example 35> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ti (atomic composition ratio Si:Sn:Ti=50:38:12) was used.
[0128] <Example 36> A gas barrier laminate was obtained in the same manner as in Example 2, except that a target formed of Si, Sn and Ti (atomic composition ratio Si:Sn:Ti=31:38:31) was used.
[0129] <Comparative Example 1> A gas barrier laminate was obtained in the same manner as in Example 1, except that a DC pulse sputtering method (referred to as method B) was used as the method for forming the transparent oxide film layer 13. In this case, flat rectangular electrodes were used, and a DC power source was used as a means for applying power to the electrodes. At that time, a pulse voltage with a frequency of 10 kHz (ON-time: 95%) was applied to the electrodes.
[0130] <Comparative Example 2> A gas barrier laminate was obtained in the same manner as in Example 2, except that a DC pulse sputtering method (method B) was used as the method for forming the transparent oxide film layer 13. At this time, a DC power source was used as a means for supplying power to the electrodes, as in Comparative Example 1. At that time, a pulse voltage with a frequency of 10 kHz (ON-time: 95%) was applied to the electrodes.
[0131] <Comparative Example 3> A gas barrier laminate was obtained in the same manner as in Example 1, except that a target made of Si (atomic composition ratio Si:Sn=100:0) was used.
[0132] <Evaluation and Method> [Measurement of film composition of transparent oxide film layer of gas barrier laminate] The film composition of the gas barrier laminates produced in Examples 1 to 36 and Comparative Examples 1 to 3 was measured using X-ray photoelectron spectroscopy (JPS-9010MX manufactured by JEOL Ltd.). In this case, composition analysis was repeated four or more times in the depth direction of the vapor deposition film using Ar ions, and the average was calculated, and Si / (Si+Sn) and O / (Si+Sn) were calculated for Examples 1 to 11 and Comparative Examples 1 to 3. In addition, Si / (Sn+α) and O / (Si+Sn+α) were calculated for Examples 12 to 36.
[0133] [Measurement of refractive index of transparent oxide film layer of gas barrier laminate] The refractive index of the gas barrier laminates produced in Examples 1 to 36 and Comparative Examples 1 to 3 was measured using an ellipsometer (VUV-VASE) manufactured by J.A. Woollam Corporation.
[0134] [Measurement of gas barrier properties of gas barrier laminate] The gas barrier laminates produced in Examples 1 to 36 and Comparative Examples 1 to 3 were measured for water vapor permeability (g / m) in an environment of 40°C / 90% RH (temperature 40°C, relative humidity 90%) using a water vapor permeability meter (AQUATRAN-Model II) manufactured by MOCON, USA, in accordance with a method conforming to JIS-K7129. 2 ·day) was measured. Helium permeability and neon permeability were measured using a pressure sensor type gas measuring device (Delta Palm DP-2MST) manufactured by Techno Lox, using a differential pressure method conforming to JIS K 7126 A method at 40℃ and 0RH%.
[0135] [Measurement results] The measurement results are shown in Tables 1 and 2 below. [Table 1] [Table 2]
[0136] Comparing Example 1 corresponding to the first embodiment with Comparative Example 1, Example 1 in which the sputtering method was Method A gave better results in terms of water vapor transmission rate, helium transmission rate, and neon transmission rate than Comparative Example 1 in which the sputtering method was Method B. Similarly, comparing Examples 2, 4, 5, 6, and 7 corresponding to the second embodiment with Comparative Example 2, Examples 2, 4, 5, 6, and 7 in which the sputtering method was Method A gave better results in terms of water vapor transmission rate, helium transmission rate, and neon transmission rate than Comparative Example 2 in which the sputtering method was Method B.
[0137] Furthermore, when comparing Example 10 corresponding to the second embodiment with Comparative Example 2, Example 10, in which the sputtering method was Method C, obtained better results in terms of water vapor permeability, helium permeability, and neon permeability than Comparative Example 2, in which the sputtering method was Method B.
[0138] Furthermore, when comparing Example 11 corresponding to the second embodiment with Comparative Example 2, Example 11, in which the sputtering method was Method D, obtained better results in terms of water vapor permeability, helium permeability, and neon permeability than Comparative Example 2, in which the sputtering method was Method B.
[0139] Furthermore, when comparing Example 1 corresponding to the first embodiment with Comparative Example 3, Example 1, in which the target and the transparent oxide film 13 layer contain Si and Sn as metal elements, showed better results in terms of water vapor permeability, helium permeability, and neon permeability than Comparative Example 3, in which the target elements and the transparent oxide film 13 layer contain only Si as a metal element.
[0140] In Example 8, sputtering was performed under a film formation pressure of 0.50 Pa, and similarly to Example 2, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0141] In Example 9, sputtering was performed under a film formation pressure of 0.05 Pa. As in Example 2, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0142] In Example 12, nitrogen gas was used simultaneously with oxygen gas as the reactive gas in the sputtering process, and good water vapor permeability, helium permeability, and neon permeability results were obtained, similar to Example 2 in which only oxygen gas was used as the reactive gas in the sputtering process.
[0143] In Examples 13, 14, and 15, targets containing Al, a metal element other than Si and Sn, were used as the metal element of the target. However, similar to Example 2 in which a target containing only Si and Sn as the metal elements of the target was used, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0144] In Examples 16, 17, and 18, targets containing Ga, a metal element other than Si and Sn, were used as the metal element of the target. However, similar to Example 2, in which a target containing only Si and Sn as the metal elements of the target was used, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0145] In Examples 19, 20, and 21, targets containing Ge, a metal element other than Si and Sn, were used as the metal element of the target. However, similar to Example 2, in which a target containing only Si and Sn as the metal elements of the target was used, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0146] In Examples 22, 23, and 24, targets containing Nb, a metal element other than Si and Sn, were used as the metal element of the target. However, similar to Example 2, in which a target containing only Si and Sn as the metal elements of the target was used, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0147] In Examples 25, 26, and 27, targets containing Ta, a metal element other than Si and Sn, were used as the metal element of the target. However, similar to Example 2, in which a target containing only Si and Sn as the metal elements of the target was used, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0148] In Examples 28, 29, and 30, targets containing W, a metal element other than Si and Sn, were used as the metal element of the target. However, similar to Example 2, in which a target containing only Si and Sn as the metal elements of the target was used, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0149] In Examples 31, 32, and 33, targets containing Zn, a metal element other than Si and Sn, were used as the metal element of the target. However, similar to Example 2, in which a target containing only Si and Sn as the metal elements of the target was used, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0150] In Examples 34, 35, and 36, targets containing Ti, a metal element other than Si and Sn, were used as the metal element of the target. However, similar to Example 2 in which a target containing only Si and Sn as the metal elements of the target was used, good results were obtained for the water vapor permeability, helium permeability, and neon permeability.
[0151] Although the embodiment of the present invention has been described in detail above, in reality, the present invention is not limited to the above embodiment, and even if there are modifications within the scope of the gist of the present invention, they are included in the present invention. [Industrial Applicability]
[0152] The gas barrier laminate according to the present invention is expected to be particularly suitable for use in fields such as electronic device-related materials, where high gas barrier properties are required. [Explanation of symbols]
[0153] 11...Resin substrate 12...Undercoat layer 13…Transparent oxide film layer 14...Overcoat layer
Claims
1. A gas barrier laminate comprising a resin substrate and a transparent oxide film layer containing silicon (Si) and tin (Sn) (excluding those containing zinc) on one or both sides of the resin substrate, The transparent oxide film layer is formed by a sputtering method using a magnetron sputtering device in which electrodes alternately serve as cathodes and anodes. The water vapor permeability at 40°C and 90% R.H. is 0.01 g / (m 2 ・day) or less, Measurement conditions: Helium permeability at 40°C and 0% R.H. is 4 cc / (m 2 .·day·atm) or less.
2. Measurement conditions: Neon transmittance at 40°C and 0% R.H. is 0.5 cc / (m 2 2. The gas barrier laminate according to claim 1, wherein the gas barrier density is 100% or less.
3. 3. The gas barrier laminate according to claim 1, wherein the ratio of the number of silicon (Si) atoms in the transparent oxide film layer to the total number of silicon (Si) and tin (Sn) atoms (Si / (Si+Sn)) is 0.10 or more and 0.62 or less, and the ratio of the number of oxygen (O) atoms to the total number of silicon (Si) and tin (Sn) atoms (O / (Si+Sn)) is 0.80 or more and 2.00 or less.
4. 3. The gas barrier laminate according to claim 1, wherein the transparent oxide film layer contains at least one element α selected from the group consisting of Al, Ga, Ge, Nb, Ta, W, Zn and Ti.
5. 5. The gas barrier laminate according to claim 4, wherein the ratio of the number of atoms of oxygen (O) to the total number of atoms of silicon (Si), tin (Sn) and the element α in the transparent oxide film layer (O / (Si+Sn+α)) is 0.90 or more and 2.50 or less, the ratio of the number of atoms of silicon (Si) to the total number of atoms of tin (Sn) and the element α (Si / (Sn+α)) is 0.10 or more and 3.50 or less, and the content (atm %) of the element α is equal to or less than the content (atm %) of silicon (Si).
6. 6. The gas barrier laminate according to claim 1, wherein the transparent oxide film layer contains nitrogen (N).
7. 7. The gas barrier laminate according to claim 1, wherein the refractive index n of the transparent oxide film layer is 1.45 or more and 1.95 or less, and the optical thickness nd expressed as the product of the film thickness d and the refractive index n is 14.5 or more and 975 or less.
8. an undercoat layer between the resin substrate and the transparent oxide film layer; 8. The gas barrier laminate according to claim 1, wherein the undercoat layer is formed from at least one of a thermosetting resin, a thermoplastic resin, an ultraviolet-curable resin, and an electron beam-curable resin.
9. an overcoat layer on the outside of the transparent oxide film layer; 9. The gas barrier laminate according to claim 1, wherein the overcoat layer is formed from at least one of a thermosetting resin, a thermoplastic resin, an ultraviolet-curable resin, and an electron beam-curable resin.
10. A method for producing the gas barrier laminate according to any one of claims 1 to 9, comprising the steps of: A method for producing a gas barrier laminate, comprising the steps of: forming a transparent oxide film layer using a magnetron sputtering apparatus in which two electrodes are positioned in parallel, and alternately positive and negative voltages can be applied to each electrode, with each electrode alternately functioning as a cathode and an anode.
11. 11. The method for producing a gas barrier laminate according to claim 10, wherein the film-forming pressure during film-forming of the transparent oxide layer is 0.05 Pa or more and 0.50 Pa or less.
Citation Information
Patent Citations
JP1973021061B1
Transparent gas barrier material and manufacturing method therefor
JP2002205354A
Gas barrier transparent resin substrate, flexible display element using it and manufacturing method of gas barrier transparent resin substrate
JP2005103768A
Steam barrier film and optical display material using the same
JP2006239884A
Sputtering film deposition system and sputtering film deposition method
JP2008007837A